EMCDDA Framework for Naming Cathinones - B. Pulver; S. Fischmann; A. Gallegos; R. Christie (Emerging Trends in Drugs, Addictions, and Health)
Introduction: The short names attributed to the 170 cathinones monitored by the EMCDDA are only loosely associated with structural features. Although related to the parent compound cathinone, one of the psychoactive principals in khat, attributing consistent, informative, and user-friendly common names to these substances is challenging. Methods: Current naming approaches were reviewed and common structural features of cathinones identified, for which abbreviations were derived from organic chemistry nomenclature and current names. Results: An EMCDDA naming framework based on the main motifs ‘cathinone’ and ‘phenone’ was developed by incorporating earlier naming approaches. The framework name of each cathinone is composed of a parent element, which, combined with information on the keto alkyl chain or the amine substitution, yields the principal name. Additional substitutions are prepended to the principal name. Other parent elements besides the two main motifs (e.g., naphthalen-2-yl) are included in the naming framework. The framework also provides exceptions for several cathinones scheduled under UN and EU legislation and structural analogs (e.g. mephedrone/4 MMC/4-methylmethcathinone). Conclusions: The EMCDDA framework on naming cathinones provides practical guidance through examples and explanations of the rationale on how consistent semi-systematic names can be derived. Owing to the structural diversity of NPS, the forensic community, researchers, and policy makers widely recognize the need for harmonized naming to achieve consensus in the denomination of NPS in legislative texts and scientific dialogue.